2021
DOI: 10.3389/fpls.2021.717077
|View full text |Cite
|
Sign up to set email alerts
|

Speed-Breeding System in Soybean: Integrating Off-Site Generation Advancement, Fresh Seeding, and Marker-Assisted Selection

Abstract: Speed breeding by artificial control of photothermal conditions facilitates generation advancement but was limited in scale and cost. In this study, we demonstrated a cost-saving off-site summer nursery pattern, taking full advantage of shorter daylength and higher temperature with lower latitude compared to the origin of the soybean cultivars used in the study. This substantially reduced the generation cycles under totally natural conditions. Using this approach, two generations of soybean cultivars from Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…In contrast, species that require the day length to drop below a certain critical threshold to induce flowering are termed short‐day plants. Speed breeding has been established for short‐day plants like soybean ( Glycine max ); however, this requires more complex protocols, involving, for example, the modification of day length, CO 2 concentration or light quality (Fang et al., 2021 ; Jähne et al., 2020 ; Nagatoshi & Fujita, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, species that require the day length to drop below a certain critical threshold to induce flowering are termed short‐day plants. Speed breeding has been established for short‐day plants like soybean ( Glycine max ); however, this requires more complex protocols, involving, for example, the modification of day length, CO 2 concentration or light quality (Fang et al., 2021 ; Jähne et al., 2020 ; Nagatoshi & Fujita, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, we establish specific growing conditions for soybean single-seed descent methods. Another perspective, we will apply the speed breeding strategy based on the result that more than 80% of the seeds germinated when freshly sown seeds of R6 were sown (Fang et al 2021). We have confirmed that more than 90% of seeds germinate when they are sown after artificially stopping water supply in R7.…”
Section: Discussionmentioning
confidence: 73%
“…Speed breeding could be used to increase breeding efficiency by shortening the breeding cycle and reducing plant space, cost, and labor resources, thereby increasing genetic gain ( Watson et al, 2018 ; Hickey et al, 2019 ). Speed breeding protocols have been established by optimizing photoperiod, daylength, and temperature in various legume crops, including soybean ( Fang et al, 2021 ), chickpea ( Samineni et al, 2019 ), pigeonpea ( Saxena et al, 2019 ), and pea ( Mobini and Warkentin, 2016 ). However, this approach has not been implemented in any underutilized legumes.…”
Section: Introductionmentioning
confidence: 99%